2008 IEEE International Symposium on Wireless Communication Systems 2008
DOI: 10.1109/iswcs.2008.4726092
|View full text |Cite
|
Sign up to set email alerts
|

On the value of synchronous downlink MIMO-OFDMA systems with linear equalizers

Abstract: Abstract-Cellular radio systems are often limited due to the presence of cochannel interference. Basically, radio systems may be operated by utilizing asynchronous or synchronous downlink transmission from all base stations in the system, where synchronization between terminals and their serving base station is mandatory in both concepts. We provide a comparison between the theoretical achievable spectral efficiency in an orthogonal frequency division multiple access systems using different linear equalizers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In [9], IRC was shown to be highly sensitive to estimation errors, since the spatial structure of the system's covariance matrix is utilized for equalization. In the following we assume quasi-static channel conditions over the observation interval.…”
Section: A Imperfect Channel Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…In [9], IRC was shown to be highly sensitive to estimation errors, since the spatial structure of the system's covariance matrix is utilized for equalization. In the following we assume quasi-static channel conditions over the observation interval.…”
Section: A Imperfect Channel Estimationmentioning
confidence: 99%
“…Hence, interference cannot be separated sufficiently, and thus SINR is systematically overestimated. However, already with a correlation window spanning N = 12 pilot symbols, 12 sectors and thus more interferers can be identified, and the SINR is determined more precisely [9]. The safety factor is then S = 0.9 dB, and the median shift becomes negligible.…”
Section: Multi-cell Performance Including Channel Estimation Errorsmentioning
confidence: 99%
“…Recently, it was shown that interference-aware minimum mean square error (MMSE) equalization helps to reduce the gap between system performance under ideal and practical conditions [11]. Equalization weights were determined from multi-cell channel estimates obtained in a synchronous 3G Long Term Evolution (3G-LTE) downlink.…”
Section: Coherent Downlink Transmissionmentioning
confidence: 99%
“…Interference covariance matrix estimation schemes have been investigated in [6], [7]. The theoretical impact of channel and interference covariance estimation errors on the performance of IRC and MMSE receivers has been studied in [6] together with the SINR distribution analysis and Gaussian noise based error model. Different procedures of the covariance estimation, namely reference signal (RS) based and user data based estimations have been summarized in [8], [7] and the references therein.…”
Section: Introductionmentioning
confidence: 99%